First Case of Patient With Two Homozygous Mutations in MYD88 and CARD9 Genes Presenting With Pyogenic Bacterial Infections, Elevated IgE, and Persistent EBV Viremia - Chiriaco, Maria; Di Matteo, Gigliola; Conti, Francesca; Petricone, Davide; De Luca, Maia; Di Cesare, Silvia; Cifaldi, Cristina; De Vito, Rita; Zoccolillo, Matteo; Serafinelli, Jessica; Poerio, Noemi; Fraziano, Maurizio; et al. (Frontiers in Immunology, 2019)
We described for the first time a female patient with the simultaneous presence of two homozygous mutations in MYD88 and CARD9 genes presenting with pyogenic bacterial infections, elevated IgE and persistent EBV viremia. In addition to defective TLR/IL1R-signaling, we described novel functional alterations into the myeloid compartment. In particular, we demonstrated a defective production of reactive oxygen species exclusively in monocytes upon E.coli stimulation, the inability of immature mono-derived DCs (iDCs) to differentiate into mature DCs (mDCs) and the incapacity of mono-derived macrophages (MDMs) to resolve BCG infection in vitro. Our data do not provide any evidence for digenic inheritance in our patient, but rather for the association of two monogenic disorders. This case illustrates the importance of using next generation sequencing (NGS) to determine the most accurate and early diagnosis in atypical clinical and immunological phenotypes, and with particular concern in consanguineous families. Indeed, besides the increased susceptibility to recurrent invasive pyogenic bacterial infections due to MYD88 deficiency, the identification of CARD9 mutations underline the risk of developing invasive fungal infections emphasizing the careful monitoring for the occurrence of fungal infection and the opportunity of long-term antifungal prophylaxis.